2020
DOI: 10.1007/s11307-020-01543-3
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Imaging of Local Inflammation: Monitoring LPS-Induced CD80/CD86 Upregulation by PET

Abstract: Purpose The co-stimulatory molecules CD80 and CD86 are upregulated on activated antigen-presenting cells (APC). We investigated whether local APC activation, induced by subcutaneous (s.c.) inoculation of lipopolysaccharides (LPS), can be imaged by positron emission tomography (PET) with CD80/CD86-targeting 64Cu-labelled abatacept. Procedures Mice were inoculated s.c. with extracellular-matrix gel containing either LPS or vehicle (PBS). Immune cell populations were analysed by flow cytometry and marker expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…CD80 can promote T cells to differentiate into Th1, while CD86 can induce Th2-mediated humoral immunity, which makes Th1/Th2 unbalanced, thus enlarging abnormal immune response [ 18 ]. In vitro experiments showed that [ 19 ], monoclonal antibody blocked CD80 and CD86 molecules and blocked CD28/B7 pathway, while cytotoxic T cell associated antigen 4 could bind to B7, thus inhibiting the proliferation of T cells. In this study, the scores of CD86, CD80, Th1, Th2, and Th1/Th2 in the death group were higher than those in the survival group, suggesting that the immune imbalance of patients in the death group was more serious.…”
Section: Discussionmentioning
confidence: 99%
“…CD80 can promote T cells to differentiate into Th1, while CD86 can induce Th2-mediated humoral immunity, which makes Th1/Th2 unbalanced, thus enlarging abnormal immune response [ 18 ]. In vitro experiments showed that [ 19 ], monoclonal antibody blocked CD80 and CD86 molecules and blocked CD28/B7 pathway, while cytotoxic T cell associated antigen 4 could bind to B7, thus inhibiting the proliferation of T cells. In this study, the scores of CD86, CD80, Th1, Th2, and Th1/Th2 in the death group were higher than those in the survival group, suggesting that the immune imbalance of patients in the death group was more serious.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this leads to CTLA-4 upregulation that competes with CD28 for CD80/86 binding, resulting in the termination of T-cell stimulation. Furthermore, CD86 is a marker for APC activation ( 47 ) and CD86 receptor downregulation can lead to an anti-inflammatory and immune-regulatory phenotype ( 48 ) and may indicate the presence of a wound healing phase following ablation therapy. With regard to CD200R+ monocytes, we detected decreased fractions following treatment with IBT, but no relevant changes following RFA.…”
Section: Discussionmentioning
confidence: 99%
“…Post-ischemic LPS administration has previously been shown to increase astroglial GFAP immunoreactivity in mice exposed to MCAO ( Sardari et al, 2020b ) or in primary mouse astrocytes ( Lin et al, 2016 ). LPS has recently been shown to increase CD86 expression in mice, as shown by positron emission tomography using the tracer abatacept ( Taddio et al, 2021 ) and in microglia or macrophages in vitro ( Ji et al, 2018 ; Liu et al, 2020 ). In CD57BL/6 mice exposed to MCAO, CD206 + microglia and macrophages gradually accumulate in ischemic brain tissue during the first-week post-stroke, subsequently replaced by CD86 + microglia and macrophages ( Hu et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%